Głos Wolnego Związkowca . biuletyn NSZZ "Solidarność" Huty Warszawa Region Mazowsze, no. 55, 1981 - ["Solidarność"], [ed. Marek Jasiewicz, Jacek Lipiński, Andrzej Święcicki] (NSZZ "Solidarność" HW, 1981)
Creation and circulation: For internal use